Sovereignty and Responsibility Power, Norms and Intervention in International Relations - Moses, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book is a critical study of the concept of sovereignty and its relationship to responsibility. It establishes a clear distinction between empirical and normative definitions of sovereignty and examines the implications of these concepts in relation to intervention, international law, and the world state.
Keywords: Politics and war; International relations; Diplomacy; Political science; Military and Defence Studies; International Relations; Diplomacy; Political Science